Technical Note: A preliminary study of dual‐tracer PET image reconstruction guided by FDG and/or MR kernels. Issue 9 (29th July 2021) - Wang, Haiyan; Huang, Zhenxing; Zhang, Qiyang; Gao, Dongfang; OuYang, Zhanglei; Liang, Dong; Liu, Xin; Yang, Yongfeng; Zheng, Hairong; Hu, Zhanli
Abstract: Purpose: Clinically, single radiotracer positron emission tomography (PET) imaging is a commonly used examination method; however, since each radioactive tracer reflects the information of only one kind of cell, it easily causes false negatives or false positives in disease diagnosis. Therefore, reasonably combining two or more radiotracers is recommended to improve the accuracy of diagnosis and the sensitivity and specificity of the disease when conditions permit. Methods: This paper proposes incorporating 18 F‐fluorodeoxyglucose (FDG) as a higher‐quality PET image to guide the reconstruction of other lower‐count 11 C‐methionine (MET) PET datasets to compensate for the lower image quality by a popular kernel algorithm. Specifically, the FDG prior is needed to extract kernel features, and these features were used to build a kernel matrix using a k‐nearest‐neighbor (kNN) search for MET image reconstruction. We created a 2‐D brain phantom to validate the proposed method by simulating sinogram data containing Poisson random noise and quantitatively compared the performance of the proposed FDG‐guided kernelized expectation maximization (KEM) method with the performance of Gaussian and non‐local means (NLM) smoothed maximum likelihood expectation maximization (MLEM), MR‐guided KEM, and multi‐guided‐S KEM algorithms. Mismatch experiments between FDG/MR and MET data were also carried out to investigate the outcomes of possible clinical situations. Results: In the simulation study, the proposed method outperformed the other algorithms by at least 3.11% in the signal‐to‐noise ratio (SNR) and 0.68% in the contrast recovery coefficient (CRC), and it reduced the mean absolute error (MAE) by 8.07%. Regarding the tumor in the reconstructed image, the proposed method contained more pathological information. Furthermore, the proposed method was still superior to the MR‐guided KEM method in the mismatch experiments. Conclusions: The proposed FDG‐guided KEM algorithm can effectively utilize and compensate for the tissue metabolism information obtained from dual‐tracer PET to maximize the advantages of PET imaging.